The perceptions of pre-service elementary teachers in joining the professional education program on science learning that accelerates disruptive era - Riyadi Riyadi; Yulianti Yulianti; I.R. Widianto Atmojo; Sri Marmoah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Education is a complex service where qualityis defined. Disorders in the educational space require better services built around the improvement of educational program quality. Professional Pre-Service Elementary Teachers (PETs) are expected to have the ability to educate in the Disruptive Era (DE). This study aims to determine the perceptions of PEP (Professional Education Program) participants towards the appropriate science learning in DE. Qualitative descriptive method was employed to obtain data. The data for this study were collected using questionnaires and open-ended questions related to science learning that accelerate DE, given to 42 PETs in the Elementary School Teacher Education Program, Universitas Sebelas Maret. Based on the analysis of questionnaires and open questions related to science learning that accelerates DE, it can be concluded that the highest perceptions of PETs in the strongly-agree category are in the aspect of dynamic ability to change by 83%; and the lowest perceptions are in the aspects of entrepreneurship skill of 52%. Based on the findings, it is recommended that it be necessary to develop appropriate science-learning support frameworks in DE.